HUBUNGAN PENERAPAN SURGICAL SAFETY CHECKLIST (SSC) DENGAN KESELAMATAN PASIEN OPERASI - joko pitoyo; Sabrina Kumala Dewi; Maria Diah Ciptaning Tyas (Poltekkes Kemenkes Malang, 2022)
Patient safety is basic of good quality health care, one of which is surgical patient safety. Surgical Safety Checklist is a checklist that has been widely applied in the surgical process to help improve the safety of surgical patient. The purpose is to find out the relationship between the application of Surgical Safety Checklist (SSC) and the safety of surgical patient. This research design uses a literature review with the systematic mapping study method. In this study, a study selection will be carried out using PRISMA flow chart that is adjusted to the inclusion and exclusion criteria, then assessment of the study quality will be carried out using the JBI Critical Appraisal, so the studies selected as literature will be accordance with the research objectives. The majority of selected studies stated that the mortality rate decreased after the application of SSC. The results from 2 studies stated that the completion of SSC in all phases could reduce readmission and reoperation rates of post operative patients, from 4 other studies it was stated that the LOS of patients was reduce by 0,6 to 1 day after the application of SSC, and from 4 studies it was stated that the post operative complication rate also decreased after the application of SSC. Result of the 9 studies selected in this literature review presented significant results in reducing mortality, post operative complication, LOS, readmission, and reoperation of patients after SSC application.